(untitled) (Biological Sciences - PJSIR, 2022)
The dishes were kept covered in dark place for 4 days at room temperature, after interval of24 hrs, one seed was taken from each pctridish and crushed in mortor with pestle in cold methanol. This process was carried out for all seeds individually and the materials was filtered separately.